Hydroformylation of 1,4-diacetoxy-2-butene using HRh(CO)(PPh3)(3) tethered on alumina as a catalyst: kinetic study - Chansarkar, Rashmi; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2009)
Hydroformylation of 1,4-diacetoxy-2-butene (DAB) was studied using [HRh(CO)(PPh3)(3)] complex catalyst tethered on alumina using phosphotungstic acid (PTA) as an anchoring agent, with the aim to understand the product distribution, selectivity, and intrinsic kinetics. It was observed that with the tethered heterogeneous catalyst a simultaneous hydroformylation followed by deacetoxylation steps was possible, which is relevant for combining two steps in the sequence of synthesis of vitamin-A intermediate [2-formyl-4-acetoxy butene (FAB)]. P-31 cross-polarization magic angle spinning nuclear magnetic resonance (CP MAS NMR) and infrared (IR) instrumental techniques were found be the most effective techniques to establish the catalyst structure and true heterogeneity. On the basis of the spectroscopic evidence, we postulate the loss of a PPh3 group during tethering to give HRh(CO)(PPh3)(2)-PTA-Al2O3 as a heterogeneous complex catalyst. Experimental data on the concentration-time and CO/H-2 consumption-time profiles were obtained and the effects of DAB concentration, CO partial pressure, H-2 partial pressure, and catalyst loading were studied in a 50 mL stirred batch reactor over a temperature range of 338-358 K. The analysis of solid-liquid-gas mass transfer effects was investigated to ensure that the reaction was operating in the kinetic regime Various models were developed, and the best model was chosen by a model discrimination procedure. The agreement between the model prediction and the experimental data was found to be excellent. The activation energies for the hydroformylation and deacetoxylation steps were found to be 42.5 and 80.2 kJ/mol.